2018
DOI: 10.1007/s11695-018-3371-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression Before and After Bariatric Surgery in Low-Income Patients: the Utility of the Beck Depression Inventory

Abstract: Almost half of bariatric surgery candidates have some degree of depression that improves dramatically soon after bariatric surgery. Such change continues stable during the first year. Improvement was independent of gender, and depression has no influence on weight loss. In low-income bariatric patients, depression is lower than reports from developed countries, but similar improvement has been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…A total of 11,255 subjects from 49 articles were included in the present meta‐analysis (Figure 1). All were prospective studies, except for one cross‐sectional 26 and three retrospective study design 27–29 . Roux‐en‐Y gastric bypass was performed in 31 studies, biliopancreatic diversion in 4, gastric banding in 24, sleeve gastrectomy in 15 and vertical gastroplasty in 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 11,255 subjects from 49 articles were included in the present meta‐analysis (Figure 1). All were prospective studies, except for one cross‐sectional 26 and three retrospective study design 27–29 . Roux‐en‐Y gastric bypass was performed in 31 studies, biliopancreatic diversion in 4, gastric banding in 24, sleeve gastrectomy in 15 and vertical gastroplasty in 7.…”
Section: Methodsmentioning
confidence: 99%
“…All were prospective studies, except for one cross‐sectional 26 and three retrospective study design. 27 , 28 , 29 Roux‐en‐Y gastric bypass was performed in 31 studies, biliopancreatic diversion in 4, gastric banding in 24, sleeve gastrectomy in 15 and vertical gastroplasty in 7. A total of 24 studies examined the proportion of anxiety symptoms and 28 studies compared the proportion of depressive symptoms pre‐ and post‐surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that individuals with obesity have a 55% greater chance of developing depression and individuals with depression have a 58% greater chance of developing obesity . Furthermore, 45% of bariatric surgery candidates present with a depressive disorder, while 56% have experienced a depressive disorder throughout their life . Higher lifetime prevalence rates have been reported among women presenting for surgery, with up to 60% experiencing a depressive disorder across the lifetime .…”
Section: Psychological Outcomes Following Surgical and Endoscopic Barmentioning
confidence: 99%
“…It has also been suggested that the incidence of psychopathologies and severe psychiatric affections is higher, being this partly responsible for the lack of adherence to the dietetic treatment and lifestyle changes. Weight loss has been related to a significative decrease in psychological symptoms [5].…”
Section: Introductionmentioning
confidence: 99%